Low salinity water injection in Berea sandstone: Effect of wettability, interface elasticity, and acid and base functionalities. (1st March 2020) - Chávez-Miyauch, Tomás Eduardo; Lu, Yingda; Firoozabadi, Abbas
Highlights: Low salinity (LSW) injection in sandstone rocks is presented in five different crude oils, two of the crudes are heated from the three crude oils. LSW injection in the water-wetting state does not give extra recovery from injection of low salinity water after high salinity water injection. Contact angles of crude oil-brine-mica reveal that the substrates are preferentially water-wet. Produced water has high pH. There is no difference in pH of produced water from LSW and HSW injection in our experiments. Salt concentration of produced water decreases due to the mixing of injected brine and connate water. Interfacial viscoelasticity data indicate that interface elasticity and effectiveness of LSW injection may be related. Recovery from LSW injection in secondary mode correlates with the base functionalities in the crude oils. Abstract: Injection of low salinity water (LSW) in oil formations may provide improved oil recovery. The mechanisms of the process are not fully understood. There is not clear understanding of what types of crude oil, rock or brine composition lead to improved oil recovery in a secondary or tertiary flooding mode. In this work, five different crude oil samples: three stock tank oils from the Middle East and two obtained by heating the original oils at 55 °C for 24 h are used in waterflooding experiments in Berea sandstone cores. We perform LSW injection in secondary and tertiary mode. Total acid number (TAN), total base number (TBN) of the crude oils, as well as contact angles between rock/oil/brine, and interfacial viscoelasticity between crude oil and brine are measured to shed light into the mechanisms of the process from LSW injection. In our experiments, there is no increase recovery in tertiary flooding mode, however, there is increased recovery in some of crude oil samples from LSW injection in secondary mode. In one of the three whole crudes, there is significant improved recovery from 53% to 66% by LSW injection in comparison to high salinity water (HSW) injection. In another whole crude, there is no increase in recovery from LSW injection and in the third whole crude, there is limited improved recovery by LSW injection. In both heated crude oils, the recovery is improved significantly; around 10% in one and about 25% in the other from LSW injection compared to HSW injection. The results from recovery are compared to contact angle, interfacial viscoelasticity, TAN, and TBN of the crude oils. There is no strong relationship between wettability alteration (based on contact angle) from LSW injection. We observe correlation with and TBN. The pH of the produced water in our experiments does not depend on the salinity of the injected brine and remains basic at all time (pH = 10). This pH observation is different from the past work in the literature.